Get ready! for standardized tests. Grade one / Math - McConnell, Sandy (New York : McGraw-Hill, 2001)
Presents information and materials for parents to help their Grade 1-level children prepare for standardized tests, covering addition, subtraction, clocks and calendars, money, geometry, fractions, measurement, and word problems, and providing test-style exercises and a practice test with answers.
"Real sample test"--Cover.
Cover title: Get ready! for standardized tests.
Includes bibliographical references (p. 79).
Professional
Keywords: Achievement tests -- United States -- Study guides; Mathematics -- Study and teaching (Elementary) -- United States; Mathematics -- Study and teaching -- Parent participation -- United States; Achievement tests -- United States -- Study guides; Mathematics -- United States -- Examinations -- Study guides; Mathematics -- United States -- Study and teaching